Global transcriptome dynamics of seagrass flowering and seed development process: insights from the iconic seagrass Zostera marina L - Zhang, Yu; Yue, Shidong; Wang, Xinhua; Liu, Mingjie; Xu, Shaochun; Zhang, Xiaomei; Zhou, Yi (Frontiers in Plant Science, 2025)
Seagrasses are the only group of higher angiosperms capable of fully living in seawater, playing a significant role in plant evolutionary history. However, studies on the molecular regulatory networks underlying sexual reproduction in seagrasses remain limited. This study evaluated the morphological changes of the spathe during eelgrass sexual reproduction and analyzed global transcriptome dynamics across eight sequential stages. The key findings are as follows:(1) Key flowering integrators such as FT, SOC1, AP1, and LFY exhibited high expression levels during the early stages, indicating their involvement in the induction of eelgrass flowering, consistent with terrestrial plants. (2) Based on the classical model of floral organ development in terrestrial plants – the “ABCDE model, genes related to the development of stamens, carpels, and ovules of eelgrass, including B-, C-, D-, and E-class genes, were identified. (3) Photosynthesis was temporarily suppressed after the initiation of sexual reproduction, and gradually resumed during the seed development stage, suggesting that the developed seed may perform photosynthesis. The Fv/Fm value (0.641 ± 0.028) of seeds at the developed seed stage further indicated that these seeds are indeed capable of photosynthesis. These findings provide important insights into the potential mechanisms underlying seagrass sexual reproduction and enrich knowledge of its reproductive genetics.